2021
DOI: 10.31258/jta.v4i1.57-72
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Supervisi Akademik Kepala Sekolah Terhadap Profesionalisme Guru Mata Pelajaran Ekonomi Sma Negeri Di Kabupaten Kampar

Abstract: This study aims to see the magnitude of the influence of principal academic supervision on the professionalism of teachers in economics. This research is limited to the state high school unit group only, because there are so many private high schools in Kampar Regency. The method used is a survey method with correlational techniques. The population in this study were all 55 teachers of the economy at SMA Negeri Kampar Regency. The data in this study were collected by distributing questionnaires and documentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…These data provide credence to the theory put forth, previous study which there is a substantial correlation between the professional competency of teachers and the academic oversight provided by school principals, with a 42,4% influence size (Kusmei et al, 2021). Additionally, other study examined the effect of academic oversight by the school principal on teachers' professional competency (Sari & Isjoni, 2021). The study showed that teachers' professional competence had a positive 49.63% influence.…”
Section: The Effect Of Principal Academic Supervision On Teacher Prof...supporting
confidence: 76%
“…These data provide credence to the theory put forth, previous study which there is a substantial correlation between the professional competency of teachers and the academic oversight provided by school principals, with a 42,4% influence size (Kusmei et al, 2021). Additionally, other study examined the effect of academic oversight by the school principal on teachers' professional competency (Sari & Isjoni, 2021). The study showed that teachers' professional competence had a positive 49.63% influence.…”
Section: The Effect Of Principal Academic Supervision On Teacher Prof...supporting
confidence: 76%